Tinjauan Kondisi Fisik dan Kemampuan Keterampilan Teknik Dasar Atlet Sepakbola SMA Negeri 2 Koto XI Tarusan Kabupaten Pesisir Selatan - RUDI HARTONO; Gusril Gusril (JURNAL STAMINA, 2019)
The problem in the research is football athlete in SMA Negeri 2 Koto XI Tarusan Kab Pesisir Selatan do es not showing their achiement in football sporti. The purpose of this of this research is 1) for looking ability in shooting 2) Knowing ability in dribbling 4) to knowing ability in endurance 5) to knowing ability in strength 6) to knowing ability in speed. The type of this research is descriptive the population is all the athlete football in SMA Negeri 2 Koto XI Tarusan Kab Pesisir Selatan total of the athlete is 25 (twenty five) person. The technique of taking sample is total sampling is all the populations are researched to knowing how the basic skill and phisical condition check the athletes researcher doing basic technique test and physical condition component. Data finalysis is using technique descriptive analysis. The results of this research is showing that rating of ability in shooting 154,68 and categorized of the number is medium. Rating ability in dribbling is 12,73. Categorized is good rating ability and controlling the ball is 12,28 categorized is medium, rating ability in athlete endurance is 15,09 categorized is medium. Rating ability in athlete strength is 75,78 categorized is low and rating ability in athlete speed is 4,69 categorized is medium.